The Students’ Ability to Solve Realistic Mathematical Problems through Polya Type Problem Solving Learning Model - I Wayan Widiana; I Gusti Ngurah Japa; I Made Suarjana; Komang Sujendra Diputra (Intelektual Pustaka Media Utama, 2018)
This study was done to analyze the effect of Polyatype problem solving learning oriented toward realistic mathematics on the ability to solve mathematical word problems. This study belongs to an experimental research with the Posttest Only Control Group Design. The population used in this study was the students of grade 4 at Gugus VIII Sukawati Gianyar elementary schools with the total number of 138. The sample was selected through random sampling. The result of selection by lottery assigned Grade 4 students of SDN 4 SingapaduKaler to the control class and Grade 4 students of SDN 1 SingapaduKaler to the experiment class. The data were collected through an essay test that had been validated. The data that had been collected were analyzed through a difference test (t-test). Based on the result of data analysis it can be concluded that the use of Polya type problem solving teaching model oriented toward realistic mathematics gave a positive effect to the ability to solve word problems among the Grade 4 students in Gugus VIII Sukawati Gianyar.